Deep Ultraviolet Emitting Scintillators for Biomedical Applications: The Hard Way of Downsizing LuPO4:Pr3+. (24th October 2018) - Espinoza, Sara; Volhard, Max‐Fabian; Kätker, Heike; Jenneboer, Heike; Uckelmann, Anne; Haase, Markus; Müller, Matthias; Purschke, Martin; Jüstel, Thomas
Abstract: Pr 3+ ‐doped LuPO4 emits UV radiation between 225 and 280 nm, where DNA shows strong absorption bands. Therefore, a systematic study of the luminescence of Pr 3+ doped LuPO4 is performed: Different doping concentrations, particles sizes, and excitation schemes (vacuum UV at 160 nm and X‐rays 50 kV, 2 mA, tungsten target) are compared. The emission spectra in the UV range depends on the excitation energy and the particle size. Microcrystalline particles (6 µm) comprising 1% Pr 3+ display the highest emission intensity at 234 nm upon vacuum UV as well as X‐ray excitation. Sub‐microscale particles (20–50 nm) of LuPO4 :Pr 3+ (1%) show the same UV emission under X‐ray excitation as the larger particles but do not emit under vacuum UV excitation. Colloidal nanoscale particles (5 nm) do not show emission in the UV‐C range. Based on the high‐density and strong X‐ray absorption of LuPO4, the implementation of Pr 3+ doped LuPO4 particles of suitable size (20–50 nm) could improve the well‐established radiation therapy. Owing to the strong absorption and low penetration depth of UV‐C radiation in biological tissue, Pr 3+ ‐doped LuPO4 particles located directly in cancerous tumors could allow for additional treatment with cell‐damaging UV‐C radiation. Abstract : Praseodymium‐doped LuPO4 emits ultraviolet radiation C (UV‐C) in the range at which nucleic acids display an absorption maximum and results in DNA damage . The goal is the best compromise between efficient emission upon X‐ray excitation and small particle size. Due to the low penetration‐depth of UV‐C in biological tissues and the particle‐size, new treatment with cell‐damaging UV‐C could be possible.